Peramalan Jumlah Kedatangan Wisatawan Mancanegara di Sulawesi Selatan Menggunakan Model ARFIMA - Sukarna; Abdy, Muhammad; Aswi; Kaito, Nurlaila (Jurusan Matematika FMIPA UNM, 2022)
Tourism is a potential and strategic asset to encourage the development of a region, especially for areas that have potential tourist objects. Exchange rates, inflation, and geography influence foreign tourist visits to an area. What may be unexpected is the increase in the number of tourists, which makes tourist workers have difficulties in providing the best services, and vice versa if there is a sudden drop, it will increase the number of unemployed. Therefore, we need a scientific study of forecasting that can provide information on the number of tourists. The ARFIMA model is an ARIMA whose differencing value is a fraction. The main goal of this research is to discover the best ARFIMA model to predict the number of foreign tourist arrivals in South Sulawesi. From the data of foreign tourists in South Sulawesi from 2015 to 2020, the result of this research is the AIC value of 710.44 for ARFIMA([1,8],d,0) with. The average difference between the actual and forecasted data in the out sample data for the two models is 38.6667 points. Therefore, the two models can still be classified as the best for forecasting foreign tourists from South Sulawesi. It depends on who applied this models into this cases.